An Appraisal of the Economic Utility of Sukuk in Financing Budget Deficits in Nigeria - Baita, Abubakar Jamilu; Mustafa, Daud (2017)
From 2000 to 2015, Nigeria has recorded an average annual budget deficit of N564.10 billion, largely financed by issuing Federal government bonds. Despite this, the country’s struggle for macroeconomic stability and overall development remains elusive and pervasive.This study appraises the economic utility and significance of sukuk (Islamic bonds) as an alternative instrument of financing budget deficits in the Nigerian economy. The study uses content and trend analysis with the secondary sources of data to achieve the objective of the study.Essentially, the study posits that the issuance of sukuk as an alternative to other interest bearing financial instruments can effectively control the historically burgeoning budget deficits and significantly complement in achieving macroeconomic and developmental objectives in Nigeria.Also, sukuk has the economic utility to promote fiscal sustainability, which is a necessary requirement for sustainable economic growth and development of any nation. The study is limited to the appraisal of sukuk in financing budget deficits in Nigeria, even though there are other sources of finance.The practical contribution of the study is that sukuk will provide an avenue for the Nigerian economy to source more funds for accelerating economic diversification.The study therefore recommends that Nigerian government should effectively and efficiently harness the potentials of Islamic bond in financing its large deficits by integrating sukuk into the fiscal sustainability strategy of the country.Also, the Federal government should encourage the state governments of Muslim populated states to adopt sukuk and integrate it as part of their fiscal strategic policies.